The Portrayal of the North-South Divide in the British Press (American & British Studies Annual, 2013)
In recent decades beginning with the 1980s, Britain has witnessed a rise in inequality accompanied by a decline in social mobility. In the course of this process the historical North-South division and its aspects have become more prominent. While the South in general has grown more affluent, the North has suffered the consequences of the closure of traditional industries in the 1980s and struggled with mass unemployment and lower living standards. The purpose of the paper is to analyse the coverage of the North-South divide by the British press, namely four major national dailies (The Times, The Telegraph, The Guardian, The Independent and The Daily Mail) as well as BBC News. The analysis is based on five indicators of the quality of life (life expectancy, poverty, education and skills, employment, housing) as postulated by social geographer Danny Dorling. The paper aims to demonstrate whether and how the portrayal of the divide is influenced by the political leanings of the individual media outlets.
Keywords: North-South divide; deindustrialization; inequality; recession; unemployment; public sector